Sealab – cocoa hand butter / Rosnani Nazri ... [et al.] - Nazri, Rosnani; I.Anthonysamy, Shameen; M.Dahalan, M.Hanif; Mohtar, N.Fazdlira; E.Zainol, Zamzila (Universiti Teknologi MARA, Kedah, 2019)
Cosmetics are aid substances used to enhance the appearance of the human body. Traditionally cosmetics include skin care, color cosmetics, hair care, nail care, oral care and perfumery and deodorants. The market of cosmetics in Malaysia is seen as a growing industry which contributes high economic growth rate that occupies the 20% market share of the global consumption value. The increasing demand for skin care drives local and imported cosmetics companies to be developing fast. For the brand owners, such as L’Oreal, Shiseido and Estee Lauder are among established in the worldwide. Cosmetics of natural origin is considering as one the best-selling cosmetics products in the country where the companies promoted them as being environment friendly, in contrast to aromatherapy which is in a limited demand. SeaLab Cocoa Hand Butter ingredients provide physical and functional properties to personal care products. Exponential growth in personal care market in Malaysia, coupled with increasing use of natural and multi-functional ingredients in these products, has been driving the country’s cosmetic ingredients market. SeaLab Cocoa Hand Butter produces a 100% organic and natural marine-based product for the consumers. It is free from artificial colorants, petrochemicals and preservatives by using mainly brown marine algae, cocoa butter, corn oil infused-based, lemon and aloe Vera extract. The product is very lightweight, durable and compact casing with economical price. Its' natural ingredients help to protects skin from excessive UV light, heals sunburn and hydrates the body skin. There's no animal testing, a respect for the environment and fair trade. SeaLab Cocoa Hand Butter safely used by people at all ages that provides rapid absorption onto all types of skin with non-greasy or sticky texture.